What price Hollywood? : gender and sex in the films of George Cukor - Helford, Elyce Rae, 1962- (The University Press of Kentucky, 2020)
The gay son of middle-class Hungarian-Jewish immigrants, George Cukor became fascinated with the theater before moving to Hollywood to become a speech coach in the early days of the sound era. Before he died in 1983, he was the noted director of nearly fifty films over a fifty-year period (1931-1981). He found steady success during Hollywood's Golden Age and beyond, including an Oscar for Best Director in 1964 for My Fair Lady - which many said was to make up for having lost the same award decades earlier for The Philadelphia Story (1940). Yet, Cukor's story is less filled with accolades than with submission to the judgements and labels given to him by the Hollywood system. As a gay man, Cukor's queerness was an open secret (much in the manner of other figures of the period like Noël Coward and Tennessee Williams) but was never proclaimed publicly in either a political or aesthetic sense. Following criticism of his focus on female-centered genres and after receiving flak for directing a woman in a man's role, Cukor quickly learned that his controversial style of directing had to change if he was to prosper. Above all, he wanted to be a Hollywood success story. In this book, the author investigates the many ways in which Cukor's films explore and comment on gender. Influenced by sexuality, race, ethnicity, class, and nation, Cukor flourished in the studio system, largely by adhering to the traditions of classical Hollywood cinema. His work has gone underexplored by academics even as he has been praised as a Hollywood "master." He was known as both an "actor's director" and a "woman's director," and he labored to get stars, including James Stewart and Judy Garland, to deliver superlative performances. The author uses a broad variety of critical and theoretical lenses to consider such subjects as female friendship, director-star collaboration, Hollywood masculinity, gender performativity, drag acts, queer musical excess, genre boundaries, and the politics of assimilation to illustrate the breadth and depth of available gendered readings of Cukor's films. --